Central amygdala neuroimmune signaling in alcohol use disorder - Mariam Melkumyan; Patrick A. Randall; Yuval Silberman (Addiction Neuroscience)
Alcohol Use Disorder (AUD) is a prevalent and debilitating condition characterized by an inability to control alcohol consumption despite adverse consequences. Current treatments for AUD, including FDA-approved medications such as naltrexone and acamprosate, have limited efficacy and compliance, underscoring the need for novel therapeutic approaches. The central amygdala (CeA) plays a crucial role in the development and maintenance of AUD, particularly aspects associated with stress and binge behaviors. Recent research indicates neuroimmune signaling in the CeA is emerging as a key factor in this process. Chronic alcohol consumption disrupts neuroimmune signaling, leading to altered cytokine expression and activation of glial cells, including astrocytes and microglia. These changes contribute to the dysregulation of neural circuits involved in reward and stress, perpetuating alcohol-seeking behavior and relapse. This review delves into how chronic alcohol exposure affects neuroimmune signaling in the CeA, contributing to the pathophysiology of AUD. By focusing on the impact of cytokine expression and glial cell activation, this review aims to elucidate the mechanisms by which neuroinflammation in the CeA influences alcohol-related behaviors. By providing a comprehensive overview of the current state of research, this review identifies potential therapeutic targets for AUD. Understanding the complex interplay between neuroimmune signaling and alcohol-related behaviors may pave the way for more effective treatments and improved outcomes for individuals struggling with AUD.